PENGAWASAN PEMERINTAH KOTA PEKANBARU TERHADAP PEMANFAATAN FUNGSI PEDESTRIAN DI KOTA PEKANBARU TAHUN 2016 - Asiah Wasillah; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Pedestrian is an area reserved for pedestrians i.e. sidewalks, pedestrian plot and no plot.The scope of this study is limited to the government's supervision of the use of pedestrian in the form of sidewalks.The sidewalks in this study refer to the ones in the center of Pekanbaru city that and sepecifically in the Ramayana shopping center area.The aim of this study is to find out the supervision that has been done by the Ministry of Transportations Communication and Informatics along with the Municipal Police of Pekanbaru toward the use of pedestrian in Pekanbaru. The data used in this study consist of primary data and secondary data with 17 informants. The informants were selected by using purposive sampling technique. The data was analyzed using descriptive qualitative method.Based on the research done by the writer, it can be concluded that the pekanbaru government’s supervisionin this case is the responsibility of the Ministry of Transportations Communication and Informatics along with the Municipal Police of Pekanbaru of the use of pedestrian, it is done through three stages of supervision, i.e. (1) Determining the pedestrian supervisory standards which are divided into three standards: determining actor supervisors, determining how to control and specifyingthe penalties of the violations. (2) Takiing assessment action. At this stage, assessment is divided into two: checking the completeness of the pedestrian facilities and disciplining the street vendors and illegal parking. (3) Doing corrections. The correction to the infraction is divided it into three: the socialization of pedestrian, increaseing the number of supervisor and finallygiving punishment to the offender. However, the number of supervisors actually is still lacking and government have yet to do the socialization about pedestrian. Also the punishments that have been given to the offender are still not explicit which results in the misuse of pedestrianhappening continuoslyand harming the pedestrians.Keywords : Supervision, Functions, Pedestrian, Walking